Parental Burnout in Hungary - Development and psychometric evaluation of the Hungarian Parental Burnout Assessment (PBA-HUN) (European Journal of Mental Health, 2022)
Introduction: Parental burnout might take place when excessive demands overwhelm the parents’ resources.Aims: To develop and validate the Hungarian version of the Parental Burnout Assessment (PBA-HUN), an instrument designed to measure parental burnout; and to determine the prevalence of parental burnout in Hungary.Methods: Data were collected via an online survey from parents with at least one child living in the household (N = 1215; 82.6% mothers; Mage = 38.68 years; SDage = 6.27 years). Confirmatory factor analysis was used to investigate the factor structure of the PBA-HUN.Results: The four-factor structure of the original PBA was replicated, confirming the following factors: exhaustion in one’s parental role, contrast with one’s parental role, feelings of being fed up, and emotional distancing from one’s children. A second-order model with a higher-order factor representing overall parental burnout also fit the data well. The internal consistency of both the subscale and total scores was excellent (α ≥ 0.84). Parental burnout had a moderately strong negative correlation with life satisfaction, and weak or moderate positive correlations with perceived stress, depression, vital exhaustion, and COVID-specific perceived stress supporting the construct validity of the PBA-HUN. The prevalence of parental burnout stood at 5.8% in this sample. The weak relationship between PBA-HUN scores and sociodemographic factors was also similar to those found in prior studies. Parental burnout correlated negatively with the number of hours spent sleeping and engaging in spare time activity, respectively.Conclusions: The PBA-HUN is a reliable and valid tool to assess parental burnout in Hungary.